2011
DOI: 10.1016/j.inhe.2011.03.010
|View full text |Cite
|
Sign up to set email alerts
|

HIV diagnoses in indigenous peoples: comparison of Australia, Canada and New Zealand

Abstract: In industrial countries, a number of factors put indigenous peoples at increased risk of HIV infection. National surveillance data between 1999 and 2008 provided diagnoses for Aboriginal and Torres Strait Islanders (Australia), First Nations, Inuit and Métis (Canada excluding Ontario and Quebec) and Māori (New Zealand). Each country provided similar data for a non-indigenous comparison population. Direct standardisation used the 2001 Canadian Aboriginal male population for comparison of five-year diagnosis rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 20 publications
1
26
0
2
Order By: Relevance
“…HIV rates reported for Indigenous peoples in Canada are higher than those reported for Indigenous peoples in Australia and New Zealand (Shea et al, 2011). Within Canada, HIV rates reported for First Nations are higher than those reported for the general population (Archibald, Sutherland, Geduld, Sutherland, & Yan, 2003;Duncan et al, 2011;Spittal et al, 2007).…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…HIV rates reported for Indigenous peoples in Canada are higher than those reported for Indigenous peoples in Australia and New Zealand (Shea et al, 2011). Within Canada, HIV rates reported for First Nations are higher than those reported for the general population (Archibald, Sutherland, Geduld, Sutherland, & Yan, 2003;Duncan et al, 2011;Spittal et al, 2007).…”
Section: Introductionmentioning
confidence: 73%
“…Within Canada, HIV rates reported for First Nations are higher than those reported for the general population (Archibald, Sutherland, Geduld, Sutherland, & Yan, 2003;Duncan et al, 2011;Spittal et al, 2007). The majority of reported HIV cases among First Nations are women (Cedar Project, Mehrabadi, et al, 2008;Shea et al, 2011), while the majority of reported HIV cases among the general population are men. These gender differences reflect differences in the HIV epidemic, which predominantly affects heterosexual and intravenous drug user subpopulations (Duncan et al, 2011) for First Nations and men-who-have-sex-with-men for the general population.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…In Canada, age standardized rates of HIV diagnosis among Canadian Aboriginal peoples have been reported at 3.9 times that of Indigenous Australians. The majority of these cases have occurred as a result of injecting drug use (Duncan et al, 2011;Shea et al, 2011;Wood et al, 2008) leading to long-standing concerns about HIV escalating among Indigenous people in Australia through injecting drug use.…”
Section: Needle and Syringe Programs (Nsps)mentioning
confidence: 99%